PENGAWASAN OTORITAS JASA KEUANGAN ATAS KEGAGALAN PENCAIRAN DANA PT EMCO ASSET MANAGEMENT: Supervisory Role of The Indonesian Financial Services Authority on Redemption Failure by PT Emco Asset Management - Alimi, Gabriela Imanuel; Abrianti, Sharda (AMICUS CURIAE, 2024)
A redemption failure has been committed by PT Emco Asset Management, especially in four equity mutual fund products that were issued and managed by the company. The supervision of investment manager companies is performed by the Indonesian Financial Services Authority (OJK) with the purpose of protecting investors. The issue to be researched is the role of supervision both preventive and repressive by OJK toward PT Emco Asset Management for the redemption failure. The type of legal research is normative, descriptive, uses secondary data that is supported by primary data, analyzes data qualitatively, and concludes with deductive logic. OJK has implemented preventive supervision by granting written instructions, but the repressive supervision is not implemented by OJK. The repressive supervision in this research is to impose administrative sanctions on PT Emco Asset Management. Therefore, OJK shall not discontinue its supervisory function towards PT Emco Asset Management.